Al-Muddaththir of the Quran Linked to the Covid-19 and Spanish Flu Pandemics: Circumstantial Evidence - Khodadoost, Baback (Journal of Quranic Sciences and Research, 2021)
ABSTRACT: Recently there have been speculations concerning a possible link between the covid-19 pandemic and Al-Muddaththir, the 74th chapter of the Quran. An examination of this chapter presented in this article shows further evidences in support of these speculations. It is shown that indications of not only the current Covid-19 pandemic, but also the horrific 1918 Spanish flu can be detected in chapter 74. The main emphasis of this article will be to demonstrate the timings of the pandemic events as they appear to have been encoded in four of the chapter verses. The concept of Translational-Coding and in particular, its use in decoding one of the time-informing verses will be explained. A remarkable scheme of Al-Muddaththir to announce the exact occurring years of the two major pandemics, will also be exposed. Coincidences of the Super Moon occurrences with major events of both, Covid-19 and Spanish flu pandemics, will be shown as the possible reason for “by the moon’ swearing in verse 74:32. In connection with these observed coincidences, possible effect of the moon’s differential gravity on suppression of the human immune system during a Super Moon occurrence will be addressed. Some other verses in Al-Muddaththir with possible relevance to the pandemic perspective of this chapter will also be discussed.